FUNCTIONALIZED MESOPOROUS SILICA: AN EFFECTIVE ADSORBENT FOR THE UPTAKE OF GOLD THIOSULFATE (Comprehensive Journal of Science, 2025)
Thiosulfate is recognized as a promising alternative lixiviant to cyanide for the extraction of gold from ore bodies. Goldthiosulfate ([Au(S2O3)2]3-), however, is not well-adsorbed by activated charcoal, making industrial scale use of thiosulfatefor gold leaching impractical at present. Because of their high specific surface areas (500-1000 m2g-1) and uniform openframeworknanoporosity (pore channel diameters in the range 3-10 nm), functionalized mesoporous silicas are widelyrecognized as highly effective materials for the selective, rapid and high capacity uptake of mercury, gold and platinumgroup ions. In the present work, the efficient and rapid adsorption of gold thiosulfate by thiol-functionalized mesoporoussilica (hereafter designated MP-HMS) is demonstrated, whereby the thiol groups in the materials bind with the goldcomplexes by ligand displacement. The adsorbed gold could be leached out using cyanide, regenerating the adsorbent forfurther uptake cycles. Functionalized mesoporous silica is thus a promising candidate for the preconcentration of goldfrom thiosulfate leachate solutions.